An in-situ K–Ar isochron dating method for planetary landers using a spot-by-spot laser-ablation technique. (1st September 2016) - Cho, Yuichiro; Sugita, Seiji; Miura, Yayoi N.; Okazaki, Ryuji; Iwata, Naoyoshi; Morota, Tomokatsu; Kameda, Shingo
Abstract: Age is essential information for interpreting the geologic record on planetary surfaces. Although crater counting has been widely used to estimate the planetary surface ages, crater chronology in the inner solar system is largely built on radiometric age data from limited sites on the Moon. This has resulted in major uncertainty in planetary chronology. Because opportunities for sample-return missions are limited, in-situ geochronology measurements from one-way lander/rover missions are extremely valuable. Here we developed an in-situ isochron-based dating method using the K–Ar system, with K and Ar in a single rock sample extracted locally by laser ablation and measured using laser-induced breakdown spectroscopy (LIBS) and a quadrupole mass spectrometer (QMS), respectively. We built an experimental system combining flight-equivalent instruments and measured K–Ar ages for mineral samples with known ages ( 1.8 Ga) and K contents (1–8 wt%); we achieved precision of 20% except for a mineral with low mechanical strength. Furthermore, validation measurements with two natural rocks (gneiss slabs) obtained K−Ar isochron ages and initial 40 Ar consistent with known values for both cases. This result supports that our LIBS–MS approach can derive both isochron ages and contributions of non-in situ radiogenic 40 Ar from natural rocks. Error assessments suggest that the absolute ages of key geologic events including the Noachian/Hesperian- and the Hesperian/Amazonian-transition can be dated with 10–20% errors for a rock containing 1 wt% K2 O, greatly reducing the uncertainty of current crater chronology models on Mars. Graphical abstract: Highlights: An in-situ K–Ar isochron dating method is developed for landing planetary missions. Laser spot analyses yield K–Ar isochron ages for rocks with precisions of 10–20%. Obtained K–Ar ages are consistent with those measured with conventional methods.